Sphingosine kinase 1–interacting protein is a dual regulator of insulin and incretin secretion. Issue 5 (21st February 2019) - Liu, Yanyan; Harashima, Shin‐Ichi; Wang, Yu; Suzuki, Kazuyo; Tokumoto, Shinsuke; Usui, Ryota; Tatsuoka, Hisato; Tanaka, Daisuke; Yabe, Daisuke; Harada, Norio; Hayashi, Yoshitaka; Inagaki, Nobuya
ABSTRACT: Our previous study demonstrated that sphingosine kinase 1–interacting protein (SKIP, or Sphkap) is expressed in pancreatic β‐cells, and depletion of SKIP enhances glucose‐stimulated insulin secretion. We find here that SKIP is also expressed in intestinal K‐ and L‐cells and that secretion of gastric inhibitory polypeptide (GIP) and glucagon‐like peptide‐1 (GLP‐1) as well as insulin are significantly increased, and blood glucose levels are decreased in SKIP‐deficient (SKIP −/− ) mice compared with those in wild‐type mice. Plasma triglyceride (Tg), LDL cholesterol, and mRNA levels of proinflammatory cytokines in adipose tissues, livers, and intestines were found to be significantly decreased in SKIP −/− mice. The phenotypic characteristics of SKIP −/− mice, including adiposity and attenuation of basal inflammation, were abolished by genetic depletion of GIP. The improvement of glucose tolerance and lipid profiles in SKIP −/− mice were cancelled by GLP‐1 receptor antagonist exendin‐(9–39) treatment. In summary, depletion of SKIP ameliorates glucose tolerance by enhancing secretion of insulin and incretins, improves lipid metabolism, and reduces basal inflammation levels. Thus, inhibition of SKIP action may emerge as a new option for treatment of type 2 diabetes mellitus with metabolic dysfunction.—Liu, Y., Harashima, S., Wang, Y., Suzuki, K., Tokumoto, S., Usui, R., Tatsuoka, H., Tanaka, D., Yabe, D., Harada, N., Hayashi, Y., Inagaki, N. Sphingosine kinase 1–interacting protein is a dual regulator of insulin and incretin secretion. FASEB J. 33, 6239–6253 (2019). www.fasebj.org